Characteristics of Pores under the Influence of Cyclic Cryogenic Liquid Carbon Dioxide Using Low-Field Nuclear Magnetic Resonance. (2nd July 2018) - Xu, Jizhao; Zhai, Cheng; Qin, Lei; Wu, Shangjian; Sun, Yong; Dong, Ruowei
Abstract : The enhancement of coalbed methane extraction by repeatedly injecting CO2 has been investigated for many decades, mostly focusing on the fracturing and flooding effect in numerous lab experiments, simulations, and field applications, whereas the effect of the accompanying heat transfer during cyclic liquid CO2 (LCO2 ) injection has rarely been studied. In this paper, the influence of the cyclic injection of cryogenic LCO2 with different cycle numbers and time on the coal pore variation was explored using low-field nuclear magnetic resonance to extract the T 2 spectral information. The results have shown that as the cycle number increased, the adsorbed water (AW) decreased while the capillary water (CW) and bulk water (BW) values increased, and the pore volumes were magnified greatly based on the tendencies of fitted polynomial curves of I sa1 values and fitted exponential curve of I sa2 values. With increasing cycle time, the increase ratios of AW, CW, and BW were not independent but mutually influenced, and the I sa1 values approximately displayed a "rapid increase-slow increase" tendency, while I sa2 roughly showed fluctuating or "increase-decrease" tendencies. The changes in the IWS and FWS showed that the increased pore connectivity could allow more water to infiltrate into the pores at the saturation state and accelerate the removal of fluid water during the centrifugation state. Theφ e andφ r variations indicated that longer cycle time coupled with a larger cycle number could cause damage generation and enhance the pore connectivity.